Tomie de Paola's book of Bible stories : New International version. - DePaola, Tomie, 1934-2020. (New York : Putnam/Zondervan, 1990)
A collection of Bible stories, from Creation to the Resurrection of Christ and the appearance of the Holy Spirit at Pentecost.
The wolf will live with the lamb -- The Old Testament -- God Creates the World -- Adam and Eve Disobey God -- Cain and Abel -- Noah and the Great Flood -- The Tower of Babel -- Abraham Offers Isaac to God -- Pharaoh's Daughter Finds Moses -- Moses and the Burning Bush -- The Israelites Cross the Red Sea -- Moses Receives the Ten Commandments -- The Fall of Jericho -- Samson and His Great Strength -- Naomi and Ruth -- David and Goliath -- Esther Saves Her People -- Daniel in the Den of Lions -- Jonah and the Great Fish -- The Lord Is My Shepherd -- The Lord Watches Over You -- Let Everything Praise the Lord -- The New Testament -- An Angel Visits Mary -- Jesus Is Born -- The Visit of the Magi -- The Boy Jesus at the Temple -- Jesus Is Baptized -- Jesus Feeds the Five Thousand -- Jesus Walks on the Water -- The Transfiguration -- The Story of the Good Samaritan -- Jesus Enters Jerusalem -- The Lord's Supper -- Jesus Prays at Gethsemane -- Jesus Dies on the Cross -- The Resurrection -- The Holy Spirit Comes at Pentecost -- Love Is Most Important -- Praise the Lord Everywhere -- Index of Bible text.
Includes index.
Keywords: Bible stories, English; Bible stories; Children's stories -- 1988.